(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article discusses the directions and principles of expanding the cognitive capabilities of future teachers in higher education institutions, increasing their cognitive activity, as well as the importance of cognitive technologies in developing intellectual activity and methodological skills of students as future teachers, with the aim of forming their methodological skills based on cognitive technologies. The article serves as a source of information for researchers. Because it offers new methods for improving the level of students’ knowledge in the process of training future teachers.